Benchmarking Trauma in Child Welfare: A Brief Report. Issue 19 (October 2022) - Dellor, Elinam D.; Yoon, Susan; Bunger, Alicia C.; Himmeger, Marla; Freishtler, Bridget
Trauma exposure is common; however, considerably higher rates are reported in some vulnerable groups including adults and children involved in child welfare systems. In this context, early screening and service linkage may ameliorate its negative impact on the physical and mental well-being of adults and children alike. Using data from two Ohio-based child welfare interventions targeting co-occurring maltreatment and substance use (Ohio START 1 and EPIC2), the purpose of this brief report was to first describe the rate of trauma exposure among participating adults (Adverse Childhood Experiences or ACEs, N = 402), children 0–5 years (CTAC, N = 271) and youth 6–18 years (CTAC, N = 177), and second to benchmark observed rates against reported rates in other child welfare or similar populations across the United States. Results show that adults were exposed to 4.2 ACEs on average, a 24% increase over previous child welfare estimates. While mean CTAC scores were not significantly different among young children ages 0–5, older children reported on average 5.6 exposures which is 27% higher than previously reported estimates. Our findings highlight the difference in risk profiles between families involved child welfare due primarily to substance misuse and those without substance misuse concerns, or where substance misuse was not the primary cause of entry. We discuss implications for service provision and time-sensitive child welfare requirements.